Edukasi Pemanfaatan Botol Plastik Bekas untuk Tanaman Hias bagi Anak-Anak di Desa Sinar Bhakti - Devi Ela Arnita; Pipit Arianti; Azzahra Astrilia Yudhita; Eka Meiliya Dona; Yulitiawati Yulitiawati (Lembaga Pengembangan Kinerja Dosen, 2025)
The problem of plastic waste has become a global issue that impacts the environment. In Sinar Bhakti Village, awareness of plastic waste management is still low, especially among children. This community service activity aims to provide education on utilizing used plastic bottles as a medium for growing ornamental plants to children in Sinar Bhakti Village. The method used is a participatory approach, directly involving children in the process of transforming used plastic bottles into planting media. The activity began with an introduction to the negative impacts of plastic waste, followed by training on plastic bottle processing techniques, and ended with practical activities of planting ornamental plants. The results of this community service showed that children were able to understand the importance of plastic waste management and practice creating planting media from used plastic bottles. Additionally, this activity enhanced creativity, environmental awareness, and a sense of responsibility among children. This activity is expected to contribute to reducing plastic waste and introducing the concept of recycling from an early age while creating a greener and more beautiful environment in Sinar Bhakti Village.